Compreensão da leitura: um estudo com alunos de 3º, 4º, 5º e 9º anos do ensino fundamental - Silva, Flávia Renata Alves da (2019)
The Simple View of Reading, proposed by Gough and Tumner (1986), stands that reading comprehension is the product of two different skills: decoding and listening comprehension (CL=DxCA). Decoding refers to the skill of corresponding each letter or group of letters to their respective phonemes, respecting the alphabetical principle. Listening comprehension refers to the capacity of understanding a text in the level of a spoken speech. The lack of either of those skills compromises reading comprehension. Considering that theoretical model for understanding the processes involved in reading comprehension, the goals of the present study were as follows: verify how reading comprehension is presented by a group of students of different grades of Elementary School (3rd, 4th,5th and 9th grades); verify how reading comprehension of words, sentences and texts improves; learn how listening comprehension is presented; verify the relation between reading comprehension of words, sentences and texts and listening comprehension. To that end, the study was conducted in a public school located in the city of São Paulo. That school keeps a good rate in IDEB and the students’ socioeconomic level is low. The study was developed in two steps: in the first step, the participant group of 312 students of 3rd, 4th, 5th and 9th grades was evaluated in reading by Test of Word Recognition (TRP) and in listening comprehension by Test of Vocabulary through Pictures (TVfusp-139r); 23 students did not show developed decoding skills and were excluded from the study. The participant group included 289 students of 3rd, 4th, 5th, and 9th grades of Elementary School with typical development, 149 girls and 140 boys. In the second step, the 289 students who participated in the study were evaluated in sentence reading comprehension (Test of Sentence Comprehension – TELCS) and text reading comprehension (TCLT1 and TCLT2). The participants showed good performance in reading comprehension of words and sentences, but they showed difficulties in both tests of text reading comprehension TCLT1 and TCLT2, where the 3rd and 4th graders showed better performance in TCLT1 than in TCLT2; the 5th and 9th graders had a better performance in TCLT2. Data showed a positive evolution in performance in those grades. It was evidenced that reading comprehension is precarious, since all participants showed difficulties in the test of text reading comprehension. Although there was progress in reading comprehension of words, sentences and texts in the different grades, data showed that the most significant change in performance of reading comprehension was from the 3rd to the 4th grade. It was also possible to observe in the present study the relation between the skills of reading words, sentences and texts and vocabulary, which was positive and significant. Results showed that, considering the Simple View of Reading, the lack of either component, decoding or listening comprehension, compromises the reading comprehension. We recognize the need of thinking about more efficient practices to teach reading as well as to develop listening comprehension and to teach reading comprehension